Mobility endpoints in marketing authorisation of drugs: what gets the European medicines agency moving?. (23rd January 2022) - Jaeger, Simon U; Wohlrab, Martin; Schoene, Daniel; Tremmel, Roman; Chambers, Michael; Leocani, Letizia; Corriol-Rohou, Solange; Klenk, Jochen; Sharrack, Basil; Garcia-Aymerich, Judith; Rochester, Lynn; Maetzler, Walter; et al.
Abstract: Background: Mobility is defined as the ability to independently move around the environment and is a key contributor to quality of life, especially in older age. The aim of this study was to evaluate the use of mobility as a decisive outcome for the marketing authorisation of drugs by the European Medicines Agency (EMA). Methods: Fifteen therapeutic areas which commonly lead to relevant mobility impairments and alter the quantity and/or the quality of walking were selected: two systemic neurological diseases, four conditions primarily affecting exercise capacity, seven musculoskeletal diseases and two conditions representing sensory impairments. European Public Assessment Reports (EPARs) published by the EMA until September 2020 were examined for mobility endpoints included in their 'main studies'. Clinical study registries and primary scientific publications for these studies were also reviewed. Results: Four hundred and eighty-four EPARs yielded 186 relevant documents with 402 'main studies'. The EPARs reported 153 primary and 584 secondary endpoints which considered mobility; 70 different assessment tools (38 patient-reported outcomes, 13 clinician-reported outcomes, 8 performance outcomes and 13 composite endpoints) were used. Only 15.7% of those tools distinctly informed on patients' mobility status. Out of 402, 105 (26.1%) of the 'main studies' did not have any mobility assessment. Furthermore, none of these studies included a digital mobility outcome. Conclusions: For conditions with a high impact on mobility, mobility assessment was given little consideration in the marketing authorisation of drugs by the EMA. Where mobility impairment was considered to be a relevant outcome, questionnaires or composite scores susceptible to reporting biases were predominantly used.